Value system and the deviant behavior of youth - Rafał Kubicki (Studia z Teorii Wychowania)
The article is an overview of relationship, which is very important from the point of view of upbringing, between the hierarchy of values preached by youth and the scale of deviant behaviors, including criminal one, that they manifest. The subject dependence, derived from various theoretical concepts, not necessarily based on the sociology of deviation or criminology (e.g. The learning theory), clearly indicates that the system of values of the youth exhibiting deviant behavior is different from the value system of adolescents whose socialization and upbringing is proceeding properly. The first mentioned group is mainly focused on the fruition of individual needs - often taking "shortcuts", they assess professional work and participation in social life differently. They highly value the so-called turbulent life (frequent changes, risks, fun, humor and momentary pleasures). They tend to accept the internal norms of their own (anti-social) group that perceives the environment in a similar way, but do not include the so-called social standards in their behaviors.